2022
DOI: 10.4317/jced.59758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of açai berry extract application on the bond strength to the bleached enamel using an experimental etch-and-rinse adhesive

Abstract: Background To evaluate the bleached enamel shear bond strength (SBS) after antioxidants application using an experimental adhesive. Material and Methods Sixty sound human molars had their roots removed then cut into buccal and lingual halves and mounted in acrylic blocks. Enamel bleaching was done using an in-office chemical bleaching agent. Specimens were arbitrarily allocated into 12 groups (n=10) regarding the three experimental levels of the study: two antioxidant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…There are several in vitro studies that used different natural antioxidants, including pine bark extract, green tea extract, grape seed extract, and lycopene, as a surface treatment following tooth bleaching and before the bonding process [21][22][23]. These studies observed that natural antioxidants enhanced the bond strength to bleached enamel; however, these antioxidants required an application time longer than 10 min [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several in vitro studies that used different natural antioxidants, including pine bark extract, green tea extract, grape seed extract, and lycopene, as a surface treatment following tooth bleaching and before the bonding process [21][22][23]. These studies observed that natural antioxidants enhanced the bond strength to bleached enamel; however, these antioxidants required an application time longer than 10 min [23].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its potential benefits, using sodium ascorbate for bonding requires an extra etching procedure with phosphoric acid [15,[17][18][19][20], which conflicts with the preference for rapid treatment among patients at present. Moreover, sodium ascorbate has a short shelf life and is highly unstable, and rapidly oxidizes after being exposed to the air [21,22]. Using a combination of antioxidant and acid etching solutions is a promising approach to reduce the total working time and improve the clinical benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation